2017
DOI: 10.1016/j.mrfmmm.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Targeted cytoplasmic irradiation and autophagy

Abstract: The effect of ionizing irradiation on cytoplasmic organelles is often underestimated because the general dogma considers direct DNA damage in the nuclei to be the primary cause of radiation induced toxicity. Using a precision microbeam irradiator, we examined the changes in mitochondrial dynamics and functions triggered by targeted cytoplasmic irradiation with α-particles. Mitochondrial dysfunction induced by targeted cytoplasmic irradiation led to activation of autophagy, which degraded dysfunctional mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…Based on the present data, TMP appeared to suppress renal ROS production and protect tubular cells against CM cytotoxicity via decreased mitophagy, autophagy, and apoptosis. There is increasing evidence to suggest that overproduction of mitochondrial ROS leads to an increase in mitochondrial fragmentation that results in tubular cell damage and apoptosis in diabetic kidney disease (DKD) [12]. Our present data are highly consistent with these findings in DKD.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Based on the present data, TMP appeared to suppress renal ROS production and protect tubular cells against CM cytotoxicity via decreased mitophagy, autophagy, and apoptosis. There is increasing evidence to suggest that overproduction of mitochondrial ROS leads to an increase in mitochondrial fragmentation that results in tubular cell damage and apoptosis in diabetic kidney disease (DKD) [12]. Our present data are highly consistent with these findings in DKD.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, we speculated that although the roles of mitophagy induction and mitochondrial fragmentation in CIN remain unknown, mitophagy may be involved in the pathogenesis of CIN. Previous work from our laboratory has shown that autophagy requires the activity of the protein Drp1 [12, 13], which was used as a marker of autophagy in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial fragmentation was observed in our research in cytoplasm‐irradiated cells, in line with the findings of Zhang et al . Furthermore, Wu et al found that the mitochondrial fragmentation inhibitor Mdivi‐1 could block cytoplasmic irradiation‐induced autophagy in SAE cells, and autophagy inhibition delayed the repair of cytoplasmic irradiation‐induced DSB . Overall, our results provided another mechanism for the protective role of mitochondrial fragmentation in decreasing cytoplasmic irradiation‐induced DSB level.…”
Section: Discussionsupporting
confidence: 91%
“…7A). Although a mechanistic association between mitochondrial dynamics and mTORC1 has not been explored in depth, it is noteworthy that a potential link was recently reported between mitochondrial fission and mTORC1-mediated regulation of autophagy in cells exposed to ionizing radiation-induced stress (Wu et al, 2017). …”
Section: Discussionmentioning
confidence: 99%